Right and left ventricular dimensions with 3 tesla cardiac magnetic resonance imaging in healthy volunteers : an exploratory pilot study - Ramli, Nor Asnani Mohd (2016)
Background: Cardiac magnetic resonance imaging (CMR) has been widely used recently. The database on normal cardiac dimensions has been established in Europe using 1.5T magnetic resonance scanner. However, there is no similar database using 3T cardiac magnetic resonance scanner and for Asian population. Objective: To evaluate the right and left cardiac ventricular dimensions in healthy volunteers with 3-Tesla magnetic resonance imaging. Methodology: Fifty subjects (25 males, 25 females) without cardiovascular diseases were evaluated with 3T magnetic resonance scanner, using a steadystate free precession sequence (balanced turbo field-echo). Result: Mean age was 28.04 for male and 30.12 for female. Right and left ventricular volumes and mass were larger in males than females. RV EDV 153.83 ± 22.67 ml vs 144.46 ± 14.92ml, RV ESV 67.58 ± 14.44 ml vs 47.58 ± 9.49 ml, RV SV 86.24 ± 11.74ml vs 66.97± 8.57 ml, RV mass 35.88 ± 8.18 g vs 26.29 ± 5.26 g. LV EDV 129.05 ± 18.3 ml vs 105.44 ± 13.91 ml, LV ESV 46.65 ± 9.56 ml vs 37.92 ± 8.39 ml, LV SV 82.42 ± 12.02 ml vs 67.52 ± 8.33ml, LV mass 107.04 ± 16.55 g vs 65.92 ± 8.49 g; (p ˂0.05 for all). There was no difference in ejection fraction of right and left ventricles between the genders. Males showed significant decrease in volume indices for both ventricles with age, while female values demonstrated no significant correlation.